1994
DOI: 10.1007/bf00195915
|View full text |Cite
|
Sign up to set email alerts
|

Human liver budesonide sulphotransferase is inhibited by testosterone and correlates with by testosterone sulphotransferase

Abstract: Budesonide, a corticosteroid used in the treatment of asthma and allergic reactions, is almost entirely cleared by metabolism in man. We describe the sulphation of budesonide in human liver and lung and provide evidences that the sulphation of budesonide is catalysed by testosterone sulphotransferase. A rapid and reproducible radiometric assay for budesonide sulphotransferase is described. Liver specimens were obtained from 35 men and 65 women and lung specimens from 2 women and 17 men. The average hepatic bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(21 reference statements)
2
7
0
Order By: Relevance
“…Little is known about glucuronosyltransferase interindividual variability and the present results and those on ethinyloestradiol (3) and zidovudine (8) are consistent with the view that glucuronosyltransferase activity is positively skewed and varies over 20-fold. Whether the glucuronosyltransferase distribution pattern is, or is not, bimodal is still open to question.…”
Section: Assayssupporting
confidence: 76%
See 1 more Smart Citation
“…Little is known about glucuronosyltransferase interindividual variability and the present results and those on ethinyloestradiol (3) and zidovudine (8) are consistent with the view that glucuronosyltransferase activity is positively skewed and varies over 20-fold. Whether the glucuronosyltransferase distribution pattern is, or is not, bimodal is still open to question.…”
Section: Assayssupporting
confidence: 76%
“…Preliminary. results on the sulphation of testosterone have shown that testosterone sulphotransferase activity is higher in men than in women (8) and the first aim of this study was to examine in detail the variability in the human liver testosterone sulphotransferase activity.…”
Section: Introductionmentioning
confidence: 99%
“…DHEA-ST is capable of conjugating both the 3␣-and 3␤-hydroxyls of hydroxysteroids, the 3-phenolic hydroxyl of estrogens, as well as the 17␤-hydroxyl of testosterone and ␤-estradiol (Falany et al, 1989). This observation is consistent with the report of Pacifici et al (1994) that human liver budesonide sulfation was inhibited by testosterone and correlated with testosterone sulfotransferase activity. To date, DHEA-ST is the only human SULT reported to sulfate testosterone.…”
Section: Discussionsupporting
confidence: 82%
“…This mechanism is thought to prolong the duration of the pharmacological effects of budesonide in the lung (Tunek et al, 1997). Another report (Pacifici et al, 1994) has shown that budesonide can be conjugated with sulfate in human liver and to some extent in lung, but the site of conjugation in the molecule, as well as the sulfotransferase (SULT 1 ) isoenzymes involved, is not known. Of particular interest in this study is the ability of human cytosolic SULTs to catalyze the sulfate conjugation of the budesonide epimers.…”
mentioning
confidence: 99%
“…It seems more likely that the reason behind both the higher levels found in our asthmatic patients and the subsequent changes after budesonide treatment are the result of enzymatic events. Metabolism of budesonide as well as salbutamol is dependent on enzymes within the sulfotransferases family (Pacifici et al 1994). Enzymatic induction at this level might be a possible explanation for the changes found in salbutamolplasma levels after budesonide.…”
Section: Discussionmentioning
confidence: 99%